Student Engagement- A catalyst in Online Learning (International Journal of Food and Nutritional Sciences, 2019)
Student engagement play an important role in any form of learning. Be it is a physical oronline learning. In case of physical form where the learner and the teacher are physicallypresent in a class room, the teacher can identify the requirements and problems of thelearner and assist in solving the problems. In case of online learning, both the learnerand the teacher are situated at distant place, it is not possible to identify the requirementsand problems of the learners.